Financially Focused Sessions for Support Interventions for Parents of Children with Disabilities - Nicole Stork-Hestad; Tiyani Rodrigo; D. Bruce Ross (Journal of Financial Therapy, 2025)
Peer-Reviewed Theory and Practice Article: The current manuscript highlights the need for and proposes a best practice model of incorporating financial therapeutic elements into support intervention programming designed to assist caregivers of families with at least one child with a disability, as recognized by the Individuals with Disabilities Act (IDEA). The current manuscript proposes adding four financially focused sessions, creating a space for the caregivers to (1) radically accept their current financial circumstances, (2) empower themselves by activating financial agency, (3) develop financial persistence, and (4) create and enact a future financial strategy. These four sessions have been designed using systemic financial therapy, a theoretical framework that applies family systems theory to financial therapy. A case vignette illustrates how to address caregivers' unique challenges in caring for an afflicted child. These challenges are worsened by significant financial stress and poor management. The vignette shows how implementing four financially focused sessions can help.
Keywords: caregivers; children with disabilities; financial stress; support interventions; financial capability